A mercantilização da paisagem natural nos Parques Nacionais do Sistema Nacional de Unidades de Conservação da Natureza - Santos, Mércia Carmelita Chagas Alves (2014)
This work, containing reflections on human-nature relationship, the perspective of the process of capitalist accumulation and in the light of geographical science and of Marxist theory , aims to analyze the relations between the state and capital , implied in the process that defines the commodification of landscape from the natural activity of ecotourism in the National Parks that are part of the National System of Conservation Units . It is noted therefore that the State, in view of the continuing need for capital expansion and responding to changes of modern times, proposed to be implemented in the National Parks and its environs, ecotourism as an economic activity capable of promoting " sustainable development . " However, this activity is the type of tourism in which nature itself is a commodity that should be consumed. The interference of the commodification of natural landscapes in the production of space these protected areas and their surroundings, with the territorial capital of the tourism demands geographers reflect the purpose of the particularities of results and contradictions of this process that transforms these spaces of accumulation territories of ecotourism, before the regime of flexible accumulation of the capital system, but also imposes question what defines it. And in this sense, it is necessary to note that the analysis of reality, without disregarding the changes observed with the rise of postmodern cultural forms, maintains the central argument is that the relationship between the state and capital that define this process. Besides the growth of visitation to National Parks, some observed in recent years related to public policy, such as a result of investments made in the Parks Program Guide , as well as related to private initiative , as investments made in some of these initiatives Conservations Units by companies that have the issue of support visitation services , supporting the continuum of this process . However, nothing guarantees that this will evolve in the future to the point of being mean to restructure the space of all the National Parks and its environs, which generally constitute the traditional territories of several and / or productive leisure activities, there view are the capitalists who, following the logic of capital, make the choices of the spaces in which they will realize their investments. The analysis highlights the fact that the actions of the State, for the development of ecotourism in protected areas that category were not followed in many of these by significant capital expenditures. But it should be noted that even before being perceived any significant interference with the territorial capital ecotourism in many National Parks, these conflicts of interests related to this process are observed, like the conflicts arising from the expropriation of areas with natural landscapes of great scenic beauty that must be turned into tourist attractions. Therefore, it is important to pay attention to the mystification around ecotourism, as well as the need to evaluate the results of this territorialization in the production of space based on social interest. And since the process being analyzed in this work, is ongoing, or even just begins, there is no pretense to launch definitive conclusions about the same, making it necessary to indicate its further analysis.